In Search of God: A Desperate View of the Conflicts of the Present - Abraham Skorka (Spirituality Studies, 2023)
Against the backdrop of ongoing social violence and war, the author presents and develops his argument for controlling human violent tendencies and channeling human vital energies into constructive and morally grounded action. The essay provides a theological perspective on these issues based on midrashic exegesis.